2004
DOI: 10.1577/m02-177.1
|View full text |Cite
|
Sign up to set email alerts
|

Predation on Juvenile Salmonids by Smallmouth Bass in the Lower Granite Reservoir System, Snake River

Abstract: We estimated the consumption of juvenile salmon Oncorhynchus spp. and steelhead O. mykiss by smallmouth bass Micropterus dolomieu in the tailrace and forebay of the Lower Granite Dam and compared this consumption with that in the two major river arms of the upper Lower Granite Reservoir, Snake River, Idaho–Washington. We examined over 9,700 smallmouth bass stomachs from April through August during 1996 and 1997. Juvenile salmonids were not a major component of smallmouth bass diets by weight and number at any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(91 citation statements)
references
References 31 publications
1
79
11
Order By: Relevance
“…The predation index is composed of two components, consumption and abundance (Miranda and Hubbard 1994;Van Den Avyle and Hayward 1999). As reported in earlier work Zimmerman 1999;Naughton et al 2004), juvenile salmonids comprised a small but consistent portion of smallmouth bass diets in the Columbia River during 2008, and the primary prey consumed by smallmouth bass continued to be sculpin. Ward and Zimmerman (1999) suggested the first evidence of any response by smallmouth bass would likely be a change in diet.…”
Section: Discussionsupporting
confidence: 66%
“…The predation index is composed of two components, consumption and abundance (Miranda and Hubbard 1994;Van Den Avyle and Hayward 1999). As reported in earlier work Zimmerman 1999;Naughton et al 2004), juvenile salmonids comprised a small but consistent portion of smallmouth bass diets in the Columbia River during 2008, and the primary prey consumed by smallmouth bass continued to be sculpin. Ward and Zimmerman (1999) suggested the first evidence of any response by smallmouth bass would likely be a change in diet.…”
Section: Discussionsupporting
confidence: 66%
“…Muskellunge most probably consumed some Atlantic salmon smolts as do esocids in other systems (Warner et al 1968;Jepsen et al 1998), but grilse or adult salmon have a low probability of being consumed based on the isotope signatures of anadromous fishes in the SJR. Many other fish predators that are significantly more abundant in the SJR (Curry and Munkittrick 2005) can consume smolts such as striped bass, M. saxatilis (Blackwell and Juanes 1998), smallmouth bass (Naughton et al 2004), brown trout, Salmo trutta (Huntingford et al 1988), and brook charr, S. fontinalis (Mohler et al 2002). The best estimate of smolt consumption by muskellunge predicted a total of 7,400 smolts consumed downstream of the Mactaquac Dam if every muskellunge ate smolts only.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, consumption of juvenile salmonids (Oncorhynchus spp.) and steelhead by Smallmouth Bass (M. dolomieu) were lower in more turbid rivers (Naughton et al 2004). Gregory and Levings (1998) concluded that higher turbidity reduced encounter and mortality rates of age-0 Pacific Salmon by piscivorous fishes.…”
Section: Discussionmentioning
confidence: 98%